Complete genome sequence of Burkholderia phenoliruptrix BR3459a (CLA1), a heat-tolerant, nitrogen-fixing symbiont of mimosa flocculosa. - CUNHA, C. de O. (2012)
The genus Burkholderia represents a challenge to the fields of taxonomy and phylogeny and, especially, to the understanding of the contrasting roles as either opportunistic pathogens or bacteria with biotechnological potential. Few genomes of nonpathogenic strains, especially of diazotrophic symbiotic bacteria, have been sequenced to improve understanding of the genus. Here, we contribute with the complete genome sequence of Burkholderia phenoliruptrix strain BR3459a (CLA1), an effective diazotrophic symbiont of the leguminous tree Mimosa flocculosa Burkart, which is endemic to South America.